Enhanced Fluid Mixing Using a Reversed Multistage Tesla Micromixer - William L., N. Buglie; Khairul Fikri, Tamrin; Nadeem Ahmed, Sheikh; Mohd Fairus, Mohd Yasin; Shahrol, Mohamaddan (Wiley-VCH GmbH, 2022)
A two-dimensonal Tesla micromixer is experimentally characterized at varying Reynolds numbers (Re) and valve stages with the aim to acquire sufficiently high mixing performance. To ease fabrication, a simplified Tesla valve design is adopted. Results show two distinctive regimes of low and high Re. In the low-Re regime, a steady incremental mixing was observed as the fluid passes by each valve, whereas an enhanced mixing was identified right in the first valve in the high-Re regime. This is predominantly due to the amplified opposing flow from the helix branch which promotes stronger chaotic advection in the main microchannel. Interestingly, the measured mixing performance was found comparable to that of three-dimensional passive micromixers reported in the literature.